Peran Otoritas Jasa Keuangan terhadap perlindungan kemanan dan kerahasiaan data pribadi nasabah pada produk perbankan di Era Digital - Erik Syaputra Johan (Mahalini: Journal of Business Law, 2025)
In Indonesia, the Financial Services Authority (OJK) oversees the banking sector to ensure the stability, efficiency, and integrity of the banking system. OJK regulates, supervises, and enforces bank compliance with regulations, focusing on consumer protection  through  transparency of  information and complaint handling. OJK also encourages financial innovation through fintech regulations and ensures that banks operate healthily and responsibly. Regulations regarding customer data confidentiality are stipulated in the Banking Law, emphasizing the importance of safeguarding customer information and deposits. The issues addressed are (1) Regulations related to the Financial Services Authority in protecting the security of customer personal data in banking products, and (2) How the Financial Services Authority addresses challenges related to customer data confidentiality in banking products amidst the development of information technology. In conclusion, the Financial Services Authority (OJK) in Indonesia is responsible for protecting the security of customer personal data in banking products. Based on Law Number 21 of 2011, OJK regulates and supervises the financial services sector, ensuring consumer protection through regulations such as POJK No. 1/POJK.07/2013, which requires financial institutions to maintain the confidentiality of customer data. Together with Bank Indonesia (BI), OJK implements regulation PBI No. 18/40/PBI/2016, which mandates that banks apply risk management to protect customer data from cyber threats.